Live Typhoid Vaccine for IBD-Patients–-Well Tolerated and with Possible Therapeutic Effect - Gunnar Nysæter Dr.; Arnold Berstad (Drug Target Insights, 2008)
Background Our incidental observation of a remarkable improvement of disease activity following vaccination against typhoid in a patient with inflammatory bowel disease (IBD) was the incentive of this pilot study. Methods Ten IBD-patients (7 with ulcerative colitis and 3 with Crohn's disease) with disease activity grade 2–10 on simple colitis index were included in the study. The use of 5-ASA and prednisolone < 12.5 mg/day, but no other immunosuppressive drugs, were allowed during the trial. Live typhoid vaccine containing Salmonella serovar Ty21a (Vivotif ®, Berna) was given in standard doses on day 1, 3 and 5. Symptoms and endoscopic findings were followed up for a 3-months-period. Results Improvement of abdominal symptoms was recorded in 8 patients after 90 days, one patient was unchanged and one slightly worse. Endoscopic findings improved in 4 patients and were unchanged in 5 patients after 90 days. No side effects were observed. Conclusion Our results indicate that a live typhoid vaccine is well tolerated by patients with IBD of moderate activity. The symptomatic and endoscopic improvements were not dramatic, but encouraging enough to warrant further studies on the potential therapeutic effect of live typhoid vaccine on patients with IBD.